Impact of incentive-based game therapy and transporting children on toy vehicle to operation theatre on reducing anxiety prior to induction of anesthesia - Ahmed Bilal Akhtar; Nabeel Najeeb, Hammad; Ghafoor, Ateeq Ur Rehman (Journal of the Pakistan Medical Association, 2023)
Objective: To see if transporting paediatric patents to operation theatres using a battery-operated vehicle decreases preoperative anxiety and reduce incidents of postoperative adverse events. Method: The study was conducted from May to August 2019 at the Shaukat Khanum Memorial Cancer Hospital and Research Centre, Lahore, Pakistan, and comprised paediatric patients aged 3-5 years assessed as American Society of Anaesthesiologists grade I and II who were scheduled to undergo elective intrathecal chemotherapy under general anaesthesia. The subjects were randomised into intervention group A and control group B. Patients in group A were part of an incentive-based game in the holding bay area and were transported to the operation theatre using a battery-operated toy vehicle. Those in group B watched a pre-decided cartoon on television screen in the holding bay and were transported further using wheel chair. Induction of anaesthesia was done in the presence of guardians in both the groups. Patient anxiety was assessed using the modified Yale Preoperative Anxiety Scale in holding bay area T0, prior to induction of anaesthesia T1, and postoperative anaesthesia-related recovery T2. Data was analysed using SPSS 22. Results: Of the 36 patients, 18(50%) were in group A; 12(66.6%) boys and 6(33.3%) girls with mean age 4.01±0.48 years. The remaining 18(50%) subjects were in group B; 13(72.2%) boys and 5(27.8%) girls with mean age 3.96 years. The difference in anxiety between the groups at T0 was non-significant (p=0.73). At T1 and T2, the scores were significantly lower group A compared to group B (p<0.05). Group A patients had better bag mask ventilation compliance at induction and remarkably less incidence of hypoxia, bronchospasm, postoperative agitation and early discharge from PACU. Conclusion: Incentive-based game therapy decreased anxiety among paediatric patients preoperatively, made them more compliant and improved postoperative recovery. Key Words: Anaesthesia, Anxiety, Children, Game therapy, Induction.